Analysis of the behaviour of a novel support system in an anisotropically jointed rock mass. (January 2019) - Hu, Xiongyu; Fang, Yong; Walton, Gabriel; He, Chuan
Abstract: When constructing an excavation, the segmental lining installed in an anisotropic rock mass is susceptible to asymmetrical pressure and substantial local instabilities. To promote liner stability in such cases, a support system that combines a segmental lining with a highly deformable expanded clay and rock bolts is proposed. A series of physical model tests were performed to study the effect of this support system. In the tests, different dip angles of the primary rock mass jointing, different thicknesses of the expanded clay and different lengths and spacings of rock bolts were considered. Variations in the internal forces and deformation of the segmental lining were recorded in each case. The distribution of the internal forces and deformation of the segmental lining were anisotropic due to the rock mass anisotropy; the maximum positive bending moment and positive deformation on the liner mainly developed in the direction normal to the stratification. By using a sufficiently thick deformable clay layer, the anisotropy of the load transferred to the segmental liner can be minimized. By adding rock bolts, the combined support system can take full advantage of the reinforcement effect of the rock bolts and the yielding effect of the deformable clay layer, and the effect of the rock bolts plus the yielding layer is greater than the sum of the two individual effects. Such a system can change the internal force and deformation distribution of the segmental lining to improve liner stability.